PENGARUH INFLASI DAN TINGKAT PENGANGGURAN TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA PERIODE 2017 – 2021 - MASDELIMA HASIBUAN; RINDI SAFIRA; NURUL JANNAH (LP2MTBM MAKARIOZ, 2022)
One of the things that determines a country's economic progress can be seen from its economic growth, because theeconomy is one of the things that becomes very important for the country, an advanced economy indicates that the welfareof citizens is also getting better. The purpose of this study is to analyze the factors that affect economic growth in Indonesia.These factors include inflation and the unemployment rate. The study used multiple linear regression analysis with data persemester in the period 2017 - 2021. In this study the authors used secondary data derived from BPS and Bank Indonesia(BI), the data collected was tested using SPSS for Windows. From the results of the study it is known that inflation andunemployment rate do not have a significant influence on economic growth in Indonesia in the period 2017 - 2021. But thisproblem is also an important problem to be solved, the policies carried out by the government in overcoming inflation and theunemployment rate must be more optimized.